Reaktualisasi Karakter Kewargaan Melalui Kampung Dolanan Nusantara: Studi Etnopedagogi di Borobudur - Sukron Mazid; Sri Haryati; Achmad Busrotun Nufus; Moh. Wahyu Kurniawan; Hartutik Hartutik (Jurnal Civic Hukum, 2026)
Traditional games as part of the nation's cultural heritage are increasingly marginalized in the modern era due to the influence of globalization and the development of digital technology, so that the noble values contained in them are starting to be less recognized by the younger generation. This problem is the main focus of the study, namely how to re-actualize traditional games as an effective means of forming national character that is relevant to the current context. This study aims to describe the role of Kampung Dolanan Nusantara in instilling character values such as mutual cooperation, honesty, responsibility, and love of the homeland through local culture-based activities. The method used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study indicate that Kampung Dolanan Nusantara not only functions as a space for cultural preservation, but also as an effective educational vehicle in instilling character values in children and adolescents through a participatory, interactive, and fun approach. This activity provides benefits in the form of the creation of an educational space based on local wisdom that is able to strengthen national identity and shape a young generation with character, adaptability, and a national spirit. These findings contribute to the development of a local culture-based character education curriculum through the integration of civic values into ethnopedagogical practices, as well as being the basis for the formulation of participatory cultural preservation policies oriented towards strengthening civic identity.